Experimental Testing of the Radiation Shielding Properties for Steel - RWASHDI, Qays Abdul Ameer Dawood; WAHEED, Faez; GUNOGLU, Kadir; AKKURT, İskender (International Journal of Computational and Experimental Science and Engineering, 2022)
The development of nuclear technology and starting it to bed used in various fields made radiation part of our life. Thus protection against radiation become one of the most important topics in physics. The purpose of this work is to measure radiation shielding properties of steel sample. In this study we measured radiation shielding properties of some steels using a gamma spectroscopy system.